Green Approaches to Extractive Metallurgy: A Novel Synthesis of Sustainable Practices - Nopriantoko, Rahadian (Metalurgi, 2024)
The realm of extractive metallurgy, a cornerstone for diverse industrial applications, has traditionally grappled with environmental challenges stemming from conventional extraction methods. This thorough literature review delves into the realm of innovative green approaches within extractive metallurgy, with the overarching goal of synthesizing sustainable practices. The introduction casts a spotlight on the environmental quandaries associated with traditional metallurgical practices, underscoring the imperative for ecologically friendly alternatives. The research methodology meticulously entails a comprehensive review of peer-reviewed literature, applying stringent criteria to handpick studies that delve into sustainable metallurgical practices. The results and discussion section intricately categorizes and dissects an array of green approaches in metal extraction, including bioleaching, ionic liquids, supercritical fluid extraction, green hydrometallurgy, electrochemical methods, and hybrid processes, providing nuanced insights into their efficacy and sustainability. Through the lens of case studies, the study sheds light on recent strides made by industries that have wholeheartedly embraced these sustainable practices, with a keen focus on unraveling their consequential environmental and economic impacts. Moreover, the study conscientiously addresses the challenges encountered in the adoption of green metallurgy and adeptly identifies latent opportunities for further development in this transformative field. The findings resonate with a resounding call for the widespread adoption of sustainable practices within extractive metallurgy, emphasizing their profound implications for both industrial application and the trajectory of future research endeavors. This expanded exploration underscores the pivotal role of environmentally conscious approaches in reshaping the landscape of extractive metallurgy, paving the way for a more sustainable and responsible future.